Perempuan Bali dalam Kontestasi Pemilu: Kuantitas vs Kualitas - Sucitawathi, I G.A.A. Dewi; Joniarta, I Wayan (Badan Riset dan Inovasi Daerah Provinsi Bali, 2019)
Women's political participation in the political stage has increased, one of which is due to the creation of the 2003 Election Law which regulates the quota of women legislative candidates at least 30 percent. The emergence of regulations that open wide avenues for women to take part in politics, in fact, is inversely proportional to the conditions of women cadres in Bali. In Bali, women who succeed in sitting in the district / city legislature can be counted by fingers. From the 2004 to 2014 elections, no more than 10 percent of Balinese women succeeded in gaining positions in the regional legislature. The number of Balinese women who participated was relatively large, but after voting (elections), only a few managed to win. So that this raises the phenomenon of Balinese female cadres being only used as a tool to fulfill the quota of political parties without being given the knowledge, motivation and fighting spirit to take careers seriously in the world of practical politics.